Treatment regimens used in the management of Helicobacter pylori in Colombia - Valladales-Restrepo,Luis Fernando (2022)
Abstract Background Helicobacter pylori infection can cause gastritis, gastric ulcers, duodenal ulcers, and gastric cancer. Its treatment involves different medications, but resistance to these treatments is increasing. It is currently considered a public health problem. Aims to identify regimens used for H. pylori eradication by age group, year of treatment and geographical region of Colombia. Methods A cross-sectional study that identified regimens used H. pylori eradication in outpatient consultations over a 6-year period based on a medication dispensing database of 8.5 million people affiliated to the Colombian Health System. The appropriate regimens were those that included a proton pump inhibitor, associated with two antibiotics recommended by clinical practice guidelines (amoxicillin, clarithromycin, levofloxacin, moxifloxacin, tetracycline, doxycycline, metronidazole, tinidazole, and furazolidone). Results A total of 12,011 patients with a diagnosis of acid-peptic disease and H. pylori infection were identified, who had undergone 12,426 eradication treatment courses. Of these, 98.0% used a proton pump inhibitor (PPI), and 91.1% used amoxicillin. A total of 56.1% of the regimens were considered adequate; of these, 42.0% were a combination of PPI, amoxicillin/clarithromycin. This regimen predominated between 2015 and 2017 for all age groups. Conclusions The management of H. pylori infection in the majority of patients is heterogeneous and inconsistent with current recommendations based on evidence of antimicrobial resistance.